Teaching Strategies and How to Study Islamic Religious Education Teaching Materials - Madanun, Tri Susanto A.; Yahiji, Kasim; Ondeng, Syarifuddin; Arif, Muh (Journal La Edusci, 2024)
The purpose of this research is to provide clarification regarding productive ways to study PAI course content by investigating different teaching styles. This study will employ a qualitative research technique. Research methodologies utilized in this study included investigating current events in their natural environments, especially in cases where the boundaries between the events and their surroundings were blurry. Data reduction, data display, and withdrawal are three essential steps in the data analysis process. To sum up. With the hope that PAI educators would be better equipped to create their own curricular materials in the future, this session will concentrate on the steps involved in making a lesson plan. The use of educator-created resources can boost educators' self-assurance when leading learning activities. As a result, they are more equipped to teach their students the skills and information necessary to develop science and technology in the classroom. The success of the pupils' learning is dependent on how well the learning activities have been going. Analysis, design, development, assessment, and revision are the five main stages in the process of making educational materials.